Analysis of financial inclusion and financial stability on economic development in APEC member countries - Putri, Nadhia Hananti; Sukarniati, Lestari; Asmara, Gea Dwi; Purna, Fitra Pasapawidya (Optimum: Jurnal Ekonomi dan Pembangunan, 2024)
Financial inclusion and financial system stability are important instruments in a country's economic development. Both financial systems are critical for developing countries to improve people's welfare, promote inclusive economic growth, and protect the financial system from shocks and crises. Financial inclusion is a measure of people's accessibility to financial products and services. Meanwhile, a stable financial system will accelerate the country's economy. Therefore, this research aims to determine the effect of financial inclusion and financial system stability on economic development in APEC member countries. The data used is in panel form using the Fixed Effect Model method. This paper takes 20 member countries of the Asia Pacific Economic Cooperation (APEC) as the research object, collect the data from 2008 to 2021. The research results show that financial inclusion has a significant effect on the economy on the penetration and usability y proxies, while the availability proxy is not significant. Furthermore, the Bank Z-score as an indicator of financial system stability also has a significant influence on the economy, followed by two additional variables, namely inflation and the Financial Development Index. The conclusion is that financial inclusion and financial system stability have a positive influence on a country's economic development. Implications of this study suggest that the bank has to expand the network in the financial sector that the community can reach, then make people believe and be confident to create accounts so that people can conduct financial transactions easily and efficiently that help to improve the economy.